From Cityscape to Cyberspace: Writing the City in Hypermedia (Journal of the Association for the Study of Australian Literature, 2013)
The article argues that hypermedia--the juxtaposition of word, image and sound, within the domain of the computer--presents a major opportunity to rethink the way we write and the way we think about writing. It refers to the Electronic Writing Ensemble and to the author's own experiments.